Contest of Views on The Myth and Belief of Ngalap Berkah in Mount Surowiti, Panceng District, Gresik, East Java - Subkhana Adzim Baqi; Moh Tahrikul Hukamak; Hilwa Adenya Assyifatul Qolbi; Luqman Al Hakim (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2022)
This article aims to examine the differences in public opinion regarding the Ngalap Blessing tradition which gave rise to a myth that developed among the community in a complex tomb or shrine of Sunan Kalijaga on Mount Surowiti, Gresik Regency, Indonesia. Differences in public opinion on the belief in Ngalap Blessing with the existence of myths are important to reveal because in the developing myths they are used as a tool in seeking the benefit of human beings by juxtaposing it with the occult sciences. What are the various view of the community regarding the supernatural figure which is believed by some people as an astral from of help sent by Sunan Kalijaga. Why is the figure of walisongo juxtaposed with the unseen science,  even though on Mount Surowiti it is related to the figure of walisongo who is close to God. The method used in this study is a qualitative method of observing the research place and in supporting the research using a phenomenological approach, an event that occurs is a social science view that places human consciousness and its subjective meaning as the focus on understanding social action. The results of this study indicate that the emergence of differences of opinion on the myth and belief of Ngalap Blessing on Mount Surowiti is nothing but a difference in understanding of a religious text that by socio-cultural conditions at the time of interpretation of former places that are considered sacred by the community.